Sosialisasi Rekam Medik Elektronik pada Fasilitas Kesehatan Tingkat Pertama - Saputro, Arief Adi; Rusidah, Yunita; Budianita, Avira (Universitas Muria Kudus, 2023)
Electronic medical record is a clinical data storage application, as a clinical decision support system, standardization of medical terms, computerized data entry, as well as medical and pharmaceutical documentation in an organized manner. The First Level Health Facility is one of the places used by patients to request health services so that they have a record of interactions with patients. So this socialization is very important to do to reduce losses in terms of time and energy for both medical record officers and patients. This community service activity is carried out in first-level health facilities by providing education and socialization provided in the form of using Electronic Medical Records. Community service activities are carried out using the presentation/lecture method at IDI Kudus Regency on June 11, 2022. The use of electronic medical records is expected to improve and strengthen services for patients, including clinical (medical) and administrative services. Information generated from electronic medical records is also useful for education, regulation formulation, research, community health management, policy support, and to support referral health services. It is hoped that the application of electronic medical records can be easily used by all officers, both from medical record officers and medical personnel, the creation of integrated patient data, no duplication of medical record numbers that can make it difficult to find patient data at the time of re-treatment and holding further socialization regarding the application electronic medical record. The benefits will be felt optimally if the application of electronic medical records is evenly distributed and is supported by updated information systems and technological materials.